The NExT trial: Protocol for a two-phase randomized controlled trial testing transcranial magnetic stimulation to augment exposure therapy for youth with OCD - Christine Conelea; Claire Breitenfeldt; Alixandra Wilens; Linda Carpenter; Benjamin Greenberg; Jennifer Herren; Suma Jacob; Charles Lewis; Nicole McLaughlin; Bryon A. Mueller; Steve Nelson; Erin O’Connor; et al. (Trials)
Abstract Background Exposure with Response Prevention (ERP) is a first-line treatment for OCD, but even when combined with first-line medications it is insufficiently effective for approximately half of patients. Compulsivity in OCD is thought to arise from an imbalance of two distinct neural circuits associated with specific subregions of striatum. Targeted modulation of these circuits via key cortical nodes (dorsolateral prefrontal cortex [dlPFC] or presupplementary motor area [pSMA]) has the potential to improve ERP efficacy by decreasing compulsions during therapy. Methods The NExT (Neuromodulation + Exposure Therapy) trial is a two-phase, multisite early-stage randomized controlled trial designed to examine whether TMS augmentation of ERP alters activity in dlPFC and/or pSMA-associated circuitry and reduces compulsions during therapy in youth with OCD age 12–21 years. Phase 1 (N = 60) will compare two different active TMS regimens with sham: A. continuous theta burst stimulation (cTBS) to pSMA vs. B. intermittent theta burst stimulation (iTBS) to dlPFC. A priori “Go/No-Go” criteria will inform a decision to proceed to Phase 2 and the choice of TMS regimen. Phase 2 (N = 60) will compare the selected TMS regimen vs. sham in a new sample. Discussion This trial is the first to test TMS augmentation of ERP in youth with OCD. Results will inform the potential of TMS to enhance ERP efficacy and enhance knowledge about mechanisms of change. Trial registration ClinicalTrials.gov NCT05931913. Registered prospectively on July 5, 2023.